(untitled) (Research, Society and Development, 2022)
The gluten-free diet is recurrently used as a strategy for the treatment of various diseases. However, the restrictions caused by it make it challenging, leading to high percentages of non-adherence. Thus, the present study aims to discuss the various factors that could impair adherence to a gluten-free diet. In this regard, a qualitative bibliographic review was conducted with the descriptors diet, gluten-free, diet adherence, treatment adherence, and challenges, in the following databases Scielo, Pubmed, Science.gov, Scopus, and Google School. Several sources were found for non-adherence to the gluten-free diet, among them: insufficient information of the consumer and food handlers, inadequacies in labels and lack of knowledge in reading them, cross-contamination, and high cost of gluten-free food, lack of availability and access to these foods and unpleasant sensory characteristics, in addition to other aspects of an individual and social nature. In this light, the variety of factors interfering in the adherence and the need for individualized care as an instrument of monitoring adherence are evident, so that assertive interventions can be applied. Moreover, further studies should focus on interventions to improve the aspects addressed and, therefore, the autonomy of these people who need to follow a gluten-free diet.